Екстремальні ситуації на об’єктах паливноенергетичного комплексу: оцінювання ризику ураження людини - Біляєв, М. М.; Біляєва, В. В.; Берлов, О. В.; Тимошенко, О. А.; Biliaiev, М. М.; Biliaieva, V. V.; Berlov, O. V.; Tymoshenko, O. A. (Український державний університет науки і технологій, 2023)
Постановка проблеми. Розглядається задача оцінювання зон ураження людей у разі виникнення екстремальної ситуації на АЗС, розташованій в людному місці м. Дніпро. Здійснюється аналіз розмірів зон теплового забруднення повітря та зони можливого ураження людей у випадку розлітання уламків, через виникнення екстремальної ситуації на АЗС. Для розв’язання задач даного класу потрібна розробка спеціалізованих математичних моделей. Мета роботи – оцінювання ризику ураження людини від метальної дії уламків під час пожежі на АЗС у випадку виникнення екстремальної ситуації. Методика. Для аналізу зон ураження під час розльоту уламків використовується числова модель, що базується на інтегруванні другого закону Ньютона для руху матеріальної точки в повітрі. На базі даної числової моделі створено комп’ютерну програму. Для аналізу зон теплового забруднення під час пожежі на АЗС використовується числове інтегрування рівняння енергії, яке враховує швидкість руху повітряних мас, коефіцієнти температуропровідності, температуру повітря на місці пожежі. Наукова новизна. Розроблено ефективну числову модель для аналізу зон ураження від метальної дії уламків. Визначено зони ураження за можливої пожежі на АЗС в м. Дніпро. Практична значущість. Розроблено програму для розрахунку динаміки руху уламків у повітрі. Це дозволяє визначати зони ураження від метальної дії уламків різного розміру. Визначено зони теплового забруднення повітря, що дозволяють оцінювати ризик термічного ураження людей. Висновки. Розроблено ефективний інструмент аналізу ризику ураження людей уламками під час пожежі на АЗС. Наведено результати обчислювальних експериментів.

Problem statement. The task of assessing the zones of human damage in the event of an extreme situation at a gas station located in a crowded place in the city of Dnipro is under consideration. An analysis of the size of thermal air pollution zones and the zone of possible injury to people in the event of flying debris, created in the event of an extreme situation at a gas station, is being carried out. To solve the problems of this class, the development of specialized mathematical models is required. The purpose of the article. Assessment of the risk of injury to a person from the throwing action of debris and in the event of a fire at a gas station in the event of an emergency situation. Methodology. A numerical model based on the integration of Newton's second law for the movement of a material point in the air is used to analyze the damage zones during the flight of fragments. A computer program was created on the basis of this numerical model. Numerical integration of the energy equation is used to analyze thermal pollution zones during a fire at a gas station. This equation takes into account the speed of movement of air masses, coefficients of thermal conductivity, air temperature at the site of the fire. Scientific novelty. An effective numerical model has been developed for the analysis of damage zones from the throwing action of debris, which are formed in the event of an extreme situation at a gas station. Damage zones in the event of a possible fire at a gas station located in the city of Dnipro have been determined. Practical significance. A program has been developed for calculating the dynamics of the movement of debris in the air, which are formed in an extreme situation at a gas station. This makes it possible to determine the damage zones from the throwing action of fragments of different sizes. Zones of thermal air pollution are defined, which allow to assess the risk of thermal damage to people. Conclusions. An effective tool for analyzing the risk of injury to people in the event of flying debris and a fire at a gas station has been developed. The results of computational experiments are presented.
Extreme situations at facilities of the fuel and energy complex: assessment of the risk of human injury
Keywords: паливно-енергетичний комплекс; АЗС; пожежа; розліт уламків; ризик ураження; теплове забруднення; fuel and energy complex; gas station; fire; flying debris; risk of damage; thermal pollution